Micro-Engineered Models of Development Using Induced Pluripotent Stem Cells - Srivastava, Pallavi; Kilian, Kristopher A. (Frontiers in Bioengineering and Biotechnology, 2019)
During fetal development, embryonic cells coaxed through a series of lineage choices at various stages which lead to the formation of the three germ layers and subsequently to all the cell types that are required to form an adult human body. Landmark cell fate decisions leading to symmetry breaking, establishment of the three axes and first differentiation into three germ layers happen after implantation, and therefore have been attributed to be a function of the embryo’s spatiotemporal 3D environment. These mechanical and geometrical cues induce a cascade of signalling pathways leading to cell differentiation and orientation. Due to the physiological, ethical and legal limitations of accessing an intact human embryo for functional studies, multiple in-vitro models have been developed to try and recapitulate the key milestones of mammalian embryogenesis using mouse embryos, or mouse and human embryonic stem cells. More recently, the development of induced pluripotent stem cells represents a cell source which is being explored to prepare a developmental model owing to their genetic and functional similarities to embryonic stem cells. Here we review the use of micro-engineered cell culture materials as platforms to define the physical and geometrical contributions during the lineage differentiation process and to study the underlying pathways. This information has applications in various biomedical contexts including tissue engineering, stem cell therapy, and organoid cultures for disease modelling.